Cereal production trends under climate change: impacts and adaptation strategies in Southern Africa - Nhamo, Luxon; Matchaya, Greenwell C.; Mabhaudhi, Tafadzwanashe; Nhlengethwa, Sibusiso; Nhemachena, Charles (MDPI, 2019)
The increasing frequency and intensity of droughts and floods, coupled with increasing temperatures and declining rainfall totals, are exacerbating existing vulnerabilities in southern Africa. Agriculture is the most affected sector as 95% of cultivated area is rainfed. This review addressed trends in moisture stress and the impacts on crop production, highlighting adaptation possible strategies to ensure food security in southern Africa. Notable changes in rainfall patterns and deficiencies in soil moisture are estimated and discussed, as well as the impact of rainfall variability on crop production and proposed adaptation strategies in agriculture. Climate moisture index (CMI) was used to assess aridity levels. Southern Africa is described as a climate hotspot due to increasing aridity, low adaptive capacity, underdevelopment and marginalisation. Although crop yields have been increasing due to increases in irrigated area and use of improved seed varieties, they have not been able to meet the food requirements of a growing population, compromising regional food security targets. Most countries in the region depend on international aid to supplement yield deficits. The recurrence of droughts caused by the El Niño Southern Oscillation (ENSO) continue devastating the region, affecting livelihoods, economies and the environment. An example is the 2015/2016 ENSO drought that caused the region to call for international aid to feed about 40 million people. In spite of the water scarcity challenges, cereal production continues to increase steadily due to increased investment in irrigated agriculture and improved crop varieties. Given the current and future vulnerability of the agriculture sector in southern Africa, proactive adaptation interventions are important to help farming communities develop resilient systems to adapt to the changes and variability in climate and other stressors.